Removal of antibiotic contaminants from water via adsorption: Analysis of equilibrium isotherms - Khim Hoong Chu; Mohd Ali Hashim; Ain Aqilah Basirun (Environmental Pollution and Management)
In this study, we evaluated the performance of three related isotherm models—the Dubinin–Radushkevich (DR), Dubinin–Radushkevich–Misra (DRM), and Dubinin–Astakhov (DA) equations—for describing the adsorption of antibiotic contaminants from water, including tetracycline, metronidazole, ofloxacin, ciprofloxacin, and chlortetracycline. We applied the models to published datasets exhibiting favorable (type I) and sigmoidal (type V) isotherm profiles. The DA and DRM equations are shown to consistently outperform the DR equation, providing maximum adsorption capacity estimates that more closely match experimental values, whereas the DR equation is shown to yield unrealistic predictions. These findings suggest that the DA and DRM equations offer more reliable alternatives to the commonly used DR equation for modeling antibiotic adsorption equilibria. Of the two, the DRM equation has practical appeal because it does not require solubility data. However, when applied to type V isotherms, some of its parameters cannot be reliably estimated, limiting its applicability.